(untitled) (Indian Journal of Public Health Research & Development, 2020)
Background: Chronic hepatitis B is a global burden disease with the mortality rate of over one million around the world because of the complication. In Indonesia the number of hepatitis B sufferers in a healthy population is estimated to reach 4-20.3%, where the figure is higher outside of Java. This study aims to analyze the description of HBeAg serological status in patients with chronic hepatitis B. Method: a descriptive study using medical records and sera of patients with chronic hepatitis B was used as primary data. The population of this study were patients with chronic hepatitis B in Gastroenterology and Hepatology Center of Dr. Soetomo General Hospital Surabaya in purposive sampling. The number of samples that fulfilled the inclusion and exclusion criteria was 82 people. Result: Most patients are between the ages of 50-59 (29,3%), males (67,1%), HbeAg loss (52,8%) receiving telbivudine (31,5%) and lamivudine (31,5%) as monotherapy for more than two years (42,1%) and have normal ALT (46,3%). Discussion: People with inactive (carriers) chronic HBsAg that are characterized by HBsAg last more than six months, also HBeAg negative, have serum ALT levels within normal limits. A temporary increase in ALT before remission can occur in some patients with chronic HBV infection after one year of treatment interruption. Conclusion: Telbivudine and lamivudine, separately as monotherapy, demonstrated greater HBeAg loss which reached within more than two years therapy.